Surface Effect on 2D Hybrid Perovskite Crystals: Perovskites Using an Ethanolamine Organic Layer as an Example - Ho, Kang‐Ting; Leung, Siu‐Fung; Li, Ting‐You; Maity, Partha; Cheng, Bin; Fu, Hui‐Chun; Mohammed, Omar F.; He, Jr‐Hau (Advanced materials (Weinheim), 2018)
Despite the remarkable progress of optoelectronic devices based on hybrid perovskites, there are significant drawbacks, which have largely hindered their development as an alternative of silicon. For instance, hybrid perovskites are well‐known to suffer from moisture instability which leads to surface degradation. Nonetheless, the dependence of the surface effect on the moisture stability and optoelectronic properties of hybrid perovskites has not been fully investigated. In this work, the influence of the surface effect of 2D layered perovskites before and after mechanical exfoliation, representing rough and smooth surfaces of perovskite crystals, are studied. It is found that the smooth 2D perovskite is less sensitive to ambient moisture and exhibits a considerably low dark current, which outperforms the rough perovskites by 23.6 times in terms of photodetectivity. The superior moisture stability of the smooth perovskites over the rough perovskites is demonstrated. Additionally, ethanolamine is employed as an organic linker of the 2D layered perovskite, which further improves the moisture stability. This work reveals the strong dependence of the surface conditions of 2D hybrid perovskite crystals on their moisture stability and optoelectronic properties, which are of utmost importance to the design of practical optoelectronic devices based on hybrid perovskite crystals. The influence of the surface effect of 2D layered perovskites before and after mechanical exfoliation is studied. The smooth 2D perovskite is less sensitive to ambient moisture and exhibits a considerably low dark current. This work reveals the strong dependence of the surface condition of 2D hybrid perovskite crystals on their moisture stability and optoelectronic properties.